An empirical investigation into characteristics of corporation’s implementing ERM practices in the UK and the significance of these characteristics’ in determining ERM adoption - Jackson, H (2012)
Enterprise Risk Management (ERM) has emerged as a new and prospering paradigm succeeding Traditional Risk Management (TRM) and offering an integrated and holistic approach to risk. However, although ERM is outwardly growing in popularity, little is known about the types of organisations implementing ERM programmes in practice. This study aims to facilitate a greater understanding of the variety of organisations adopting ERM in the UK, the characteristics of these organisations and the influence these characteristics have on ERM adoption. More specifically, the study will firstly investigate whether any significant differences exist between the characteristics of ERM adopters and those firms that have no ERM programme in place. Subsequently, a binary logit regression will be performed to investigate the significance of these characteristics in determining ERM adoption. Based on empirical evidence the following conclusions have been drawn. Firstly, the comparative study between a sample of ERM adopters and non-adopters highlighted statistically significant differences between a number of firm and industry characteristics, including; presence of a CRO and risk committee, firm complexity, firm size, leverage and industry sector. Consistent with previous studies in the area, the logit regression also identified presence of a CRO and risk committee, industry sector, firm size and leverage as significant factors in determining ERM adoption.